SCHOOL, PANDEMIC AND DIGITAL TECHNOLOGIES: EXPERIENCES OF TWO YOUNG HIGH SCHOOL STUDENTS IN MEXICO CITY - María Elsa Guerrero Salinas; Claudia Patricia Valdivia Sánchez (Universidad Nacional del Nordeste, 2022)
Given the scarce existence of studies that tell the experiences of students attending school during the Covid-19 pandemic in Mexico, this research seeks to analyze from a qualitative perspective the experiences of two young high-school students when attending their classes with digital technologies during confinement. From the Socio-Cultural Theory we narrate and examine the educational activities and the different ways in which students participate. The findings show, on one hand, that young people face exercises saturation, tedious dynamics, and a limited participation in sending and receiving homework and, on the other, that when they had the opportunity to give a small twist to their activities, they did. This reveals that distance classes did not represent major transformations of what happened in the face-to-face format, which leads us to pose new challenges to transform educational practices.